THE MAKING OF SMART TOWEL TO LEARN ENGLISH VOCABULARY FOR ELEMENTARY SCHOOL STUDENTS - Bobrizal Bobrizal; Boni Saputra (INOVISH JOURNAL, 2017)
Abstract: Mastering English vocabulary is essential in this competitive world. By mastering English vocabulary, students can learn English and comunicate with people. However, there are still many of the students cannot learn English Vocabulary well. They still face difficulties for example, in learning simple daily words. This situation, make students feel bored and lose their interest in learning English. Therefore, the use of learning media are needed to attract these learners attention and interest to learn English in more effective and interesting way. Besides, media can be used to learn English anywhere and anytime outside the school. Related to this research, the main purpose of this project is to make Smart Towels which can be used as an alternative self-learning medium in learning English Vocabulary. This project resulted Smart Towels consists of various themes suitable for Elementary School Students. These towels are modified from ordinary towels that is modified to make it look more interesting. These media can be used in and outside classes during learning-teaching process or spare time. By using this media, the students can be atttracted to learn and increase their ability in English vocabulary interestingly and effectivelyÂ Keywords: Smart Towels ,learning, Vocabulary.